A method for representation of component geometry using discrete pin for reconfigurable moulds - Wang, Y.; Wang, Z.-J.; Gindy, Nabil (Elsevier, 2011)
Moulding plays a paramount role in our daily life. Traditional moulding is often dedicated and expensive. As the current market trend moves from mass production towards small batch and large variation production, the demand for a mould that can reconfigure itself for different components is greater than ever. The reconfiguration of mould is often realized through discrete pins. Previous research in that field had focused on the hardware of pin actuation in order to move pins up or down to represent different components and lock the pins at certain positions. Little research has been conducted into support software development that enables rapid reconfiguration of discrete pins to represent component geometry.This paper addresses a new method of software development for the reconfigurable mould utilising discrete pins. The overall aim of the method is to provide an interface for generic discrete pin tooling in order to enable quick reconfiguration of the mould to represent component geometry. The software is composed of three parts: part discretization, pin matrix construction and adjustment and pin matrix verification.